Moldovan Ethnographic Science (the Second Half of the 20th Century) about the Traditions and Folk Culture of the Romanians (Moldovans) from Chernivtsi Region (Ukraine) - Antoniy Moysey; Yulia Rusnak; Tetyana Nykyforuk (Codrul Cosminului, 2018)
This paper aims to analyse the contribution of folklorists and ethnographers from Republic of Moldova to studying the traditional culture of the Romanian-speaking population in the Chernivtsi region (Ukraine). There are presented the general results of a large expeditionary campaign in the second half of the 20th century and the main conclusions of scholars such as G. Spătaru, N. Băieșu, E. Junghietu, G. Botezatu, A. Hîncu, and I. Filip. In their works, they have approached almost all aspects of spiritual culture: from the folk prose, sayings, riddles, poems of calendar rituals, to the folklore of children, melodic genre, folk theatre, customs and family ceremonies, spells, riddles, magic practice, musical instruments, and instrumental music, etc.